A Critical Analysis of Structuralist Variations in Academic Writing - Muhammad Asim Mahmood, Shahla Qasim, Zahida Hussain (Journal of Research in Humanities, 2023)
This paper investigated the generic features of conclusion sections in M Phil theses written by the University students of Pakistan. The corpus constituted 60 M Phil theses from Science and technology (ST) and Humanities and Social sciences (HSS) disciplines. Models presented by Yang and Allison (2003) and Bunton (2005) were used as guiding principles. Findings revealed that most of the conclusion sections exhibited four- move structure: consolidation of research space as an obligatory move, introductory restatement, practical implication and future research as optional moves. Difference was observed in the occurrence of Move 4 (future research) in ST conclusions of this study (19.9%) and Bunton’s (80%) inferring that Pakistani students seemed unaware of the importance of relating their findings with the outer world. Move-5 (concluding restatement in Bunton’s model) was not found in Pakistani corpus suggesting the variability in written discourse specific to context. The study may serve as a useful material from pedagogical perspective for the students to get familiarized with the generic features of concluding chapters